2001
DOI: 10.1038/sj.cdd.4400874
|View full text |Cite
|
Sign up to set email alerts
|

ATM, a central controller of cellular responses to DNA damage

Abstract: Mutations in the ATM gene lead to the genetic disorder ataxiatelangiectasia. ATM encodes a protein kinase that is mainly distributed in the nucleus of proliferating cells. Recent studies reveal that ATM regulates multiple cell cycle checkpoints by phosphorylating different targets at different stages of the cell cycle. ATM also functions in the regulation of DNA repair and apoptosis, suggesting that it is a central regulator of responses to DNA double-strand breaks. Cell Death and Differentiation (2001) 8, 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
162
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(168 citation statements)
references
References 191 publications
(180 reference statements)
1
162
0
3
Order By: Relevance
“…Recent studies have shown that DNA double-strand breaks are recognized by ATM, and activated ATM mediates phosphorylation of various nuclear proteins, including p53, CHK2/Cds1, BRCA1, NBS1, and histone H2AX (Jackson, 2002;Zhou and Elledge, 2000;Khanna et al, 2001;Shiloh and Kastan, 2001;Shiloh, 2003 Figure 2 Induction of PUCR by ionizing radiation. Radiationinduced DNA double-strand breaks give rise to altered chromatin structure within the nucleus, through the process of DNA repair which is called PUCR.…”
Section: Induction Of Delayed Effectsmentioning
confidence: 99%
“…Recent studies have shown that DNA double-strand breaks are recognized by ATM, and activated ATM mediates phosphorylation of various nuclear proteins, including p53, CHK2/Cds1, BRCA1, NBS1, and histone H2AX (Jackson, 2002;Zhou and Elledge, 2000;Khanna et al, 2001;Shiloh and Kastan, 2001;Shiloh, 2003 Figure 2 Induction of PUCR by ionizing radiation. Radiationinduced DNA double-strand breaks give rise to altered chromatin structure within the nucleus, through the process of DNA repair which is called PUCR.…”
Section: Induction Of Delayed Effectsmentioning
confidence: 99%
“…This disease is associated with an elevated risk of malignancy, primarily leukaemias and lymphomas, and a high radiosensitivity. The gene defective in this syndrome, ATM (AT mutated), encodes a nuclear 350 kDa phosphoprotein containing a carboxy terminus phosphatidylinositol 3 0 -kinase (PI-3 0 kinase) catalytic domain shared by members of a superfamily of large eukaryotic proteins involved in intracellular signalling, DNA damage-induced cell cycle checkpoints, DNA repair and recombination (reviewed in Khanna et al, 2001). After exposure of cells to ionising radiation (IR) or radiomimetic drugs, ATM's kinase activity increases several-fold, although the protein level remains unchanged.…”
mentioning
confidence: 99%
“…The complexity of A-T is reflected in the cellular phenotype including reduced cell lifespan in culture, chromosomal instability, hypersensitivity to IR and radiomimetic agents, defective radiation-induced checkpoints at the G 1 , S and G 2 phases of the cell cycle, and defects in several signal transduction pathways. 4,5 The responsible gene, ATM (ataxia-telangiectasia mutated), was cloned in 1995 and occupies 150 kb of genomic DNA coding for a 13 kb mRNA with an open reading frame of 9.165 kb. 6 ATM is a 370 kD protein with a carboxy-terminal domain homologous to the catalytic subunits of phosphatidylinositol 3-kinases (PI-3Ks).…”
Section: Introductionmentioning
confidence: 99%